Antimicrobial peptides as a possible interlink between periodontal diseases and its risk factors: A systematic review. (8th October 2017) - Li, S.; Schmalz, G.; Schmidt, J.; Krause, F.; Haak, R.; Ziebolz, D.
Abstract : Antimicrobial peptides (AMPs) play a critical role in controlling innate and acquired immune responses. Local dysregulation of AMP is implicated in the pathogenesis of periodontal diseases as a response to periodontal pathogen challenge. Changes in AMP expression also characterize tobacco smoking, diabetes mellitus, obesity and rheumatoid arthritis, which are established risk factors of periodontal diseases, suggesting AMP may act as putative mechanistic links between these. The aim was to evaluate and summarize critically the current evidence pertaining to interrelationships between AMPs, periodontal diseases and selected periodontal disease risk factors. General and theme specific keywords were used to search the PUBMED database for studies relevant to AMP, periodontal diseases, smoking, diabetes mellitus, obesity and rheumatoid arthritis and critically reviewed. A total of 131 abstracts and 119 full text articles were screened for relevance; 13 studies were selected for inclusion after critical review. Local AMP dysregulation characteristic to periodontal diseases appears to occur within a broader landscape of complex systemic immune perturbations independently induced by smoking, metabolic and rheumatoid disease. The nature of these interactions and mechanistic pathways involved are inadequately understood. AMPs could be possible mechanistic interlinks between periodontal diseases and its risk factors. However, such evidence is very limited and more in vivo and in vitro studies are necessary to clarify the nature of such relationships. A greater understanding of AMPs as shared mediators is essential for unraveling their value as therapeutic or biomarker candidates.